This is the concept of algebra, the solution of the given expression will be given as follows;
-5x+2x²=-6x
adding 5x on both sides we get
5x-5x+2x²=-6x+5x
2x²=-x
divide both sides by 2
(2x²)/2=-x/2
x²=-x/2
divide both sides by x
(x²)/x=-x/(2x)
x=-1/2
the answer is x=-1/2
Answer:
M^4
Step-by-step explanation:
Here use product law which state- same base power should add
M^7-3
M^4
You add two equations together to eliminate a variable. This particular problem is nice, because it's already setup to eliminate X.
3x - 4y = 9
<span>-3x + 2y = 9
</span>
When we add these two together, 3x - 3x cancels each other out, leaving us with 0x, or nothing.
We continue with -4y + 2y (leaves us with -2y) and 9+9 (18).
-2y = 18
18/-2 = -9.
Now we have y = -9, and we can go back into the problems to solve for x.
<span>3x - 4(-9) = 9
</span>
3x + 36 = 9.
3x = -27
x = -9.
Confirm with the final equation:
-3(-9) + 2(-9) = 9
27 - 18 = 9
9 = 9 --- Confirmed.
Answer:
I would say C not to sure tho
I think that will be the answer and the graph i take it for leter